Homoepitaxial growth of thick Si-doped β-Ga2O3 layers using tetramethylsilane as a dopant source by low-pressure hot-wall metalorganic vapor phase epitaxy - Junya Yoshinaga; Yoshiki Iba; Kakeru Kubota; Yuma Terauchi; Takahito Okuyama; Shogo Sasaki; Kazutada Ikenaga; Takeyoshi Onuma; Masataka Higashiwaki; Kazushige Shiina; Shuichi Koseki; Yuzaburo Ban; et al. (Applied Physics Express)
By using tetramethylsilane (TMSi) as a Si dopant source, thick intentionally Si-doped β -Ga _2 O _3 homoepitaxial layers were grown by low-pressure hot-wall metalorganic vapor phase epitaxy. The Si concentration was linearly controlled by varying the TMSi supply, and a RT electron density nearly equal to the Si concentration was achieved in the range from 1.8 × 10 ^16 to 1.3 × 10 ^19 cm ^–3 . For the layer with a Si concentration and RT electron density of 1.8 × 10 ^16 cm ^–3 , the RT electron mobility of 136 cm ^2 ​​​​​ V ^–1 s ^–1 was found to be limited by polar optical phonon scattering.